“THEY DO NOT WANT TO PAY RESPECT AND OBEDIENCE BECAUSE OF BEING A WOMAN ...”. CACICA AND JUDICIAL PRACTICES IN LAW SUITS ‘PUEBLOS DE INDIOS’. CENTRAL CHILE, LATE EIGHTEENTH CENTURY - Cerón Sandoval, Jeniffer (Revista de Historia Social y de las Mentalidades, 2016)
This article aims to reveal the role of some women in the ’Indian peoples’ of Central Chile in the late eighteenth century. Through a case of study, we propose an analysis of judicial practices –or legal culture– by cacicas and ‘indians’. In these particular cases, the ability of these women had to defend themselves against lawsuits that confronting their communities or againts the landowners is enhaced.